Addition of Modified Lemaire Lateral Extra-Articular Tenodesis in a Single stage Revision Anterior Cruciate Ligament Reconstruction using Peroneus Longus Tendon: A Prospective Study - Sonarkar SS; Stanley A; Kumar-Singh S; Garg R; Narula A; Raj M (Malaysian Orthopaedic Journal)
Introduction: The purpose of this study is to assess the outcomes of patients that underwent single-stage revision ACL reconstruction (ACLR) with peroneus longus tendon (PLT), augmented with lateral extra-articular tenodesis (LET) using the modified Lemaire technique. Materials and methods: All the 18 patients underwent arthroscopic single-stage revision ACLR using autologous PLT with an additional modified Limier LET procedure. Patients were thoroughly assessed pre- and post-operatively by the Lachman test, the pivot shift test, and the side-to-side difference by the Rolimeter. Functional evaluation was done with the help of the Lysholm score, the IKDC subjective score, Tegner score, VAS score, MARX activity rating scale and The American Orthopaedic Foot and Ankle Society (AOFAS) score. Post-operatively, patient satisfaction, return to sport, and physical activity were also recorded. SPSS ver. 22.0 software was used. Wilcoxon test, paired and unpaired t-tests were used to compare variables. Statistical significance was determined by a two-sided p-value <0.05. Results: Regarding subjective evaluations; post-operative residual laxity, and return to sport and physical activity, all of the patients demonstrated excellent results. Post-operatively, there was significant improvement in the anterior knee laxity. According to the Marx Activity Rating Scale, the extent of sports engagement was significantly increased at 18months following surgery (p<0.001). According to the AOFAS score (p=0.38), there were no documented significant donor site morbidities. Conclusions: Single-stage revision ACLR using PLT with an additional modified Lemaire LET procedure results in a significant reduction in residual knee laxity with good clinical outcomes and a high return to play and physical activity.